Um diploma de doutor a não "herdeiros": um estudo sobre impactos de cursos de alto prestígio da UFMG para egressos das camadas populares - Beatriz Lopes Falcao (2012)
This study problematize the impacts that graduating from UFMG highly regarded schools has upon alumni from the working classes, namely: Medical School, Law School and Engineering School (specifically Chemical Engineering). Taking into account the peculiarities of this social group regarding schooling (Portes, 1993; 2001; Viana, 2007) and its presence in the Brazilian higher education, it was investigated the instrumental impacts of an academic degree, which were professional qualification and income, as well as the possible secondary effects within a framework of social mobility through education, such as the cultural consumption of some symbolic goods like literature, theater and cinema and the formation of a social capital, in a bourdieusian sense. This master's thesis came from the hypothesis that a long educational process, especially by attending such schools that enjoy potential recognition for financial gains and probability for a working position (Neri, 2007), might be broader than learning a trade itself and receiving a credential for a given profession. Such process may also have an impact in the thinking and judging categories, and consequently in social actions and interactions among individuals, resulted from the recurrent socialization and interaction with a social group with cultural heritage and economic assets differing from the individuals who were analyzed (Lahire, 2006). The research relied on the qualitative approach as methodological strategy, carrying out 16 semi-structured interviews with professionals in these areas, establishing an empirical corpus of 06 interviews carried out with doctors, 05 with lawyers/law graduates and 05 with chemical engineers. Understanding the surveyed individuals' trajectories as exception, and their unfolding into specific professions withing the occupational and symbolic hierarchy, this research relied on Pierre Bourdieu and this authors update by Bernard Lahire, as well as Brazilian productions about extensive learning within working class environments and regarding the impact of an academic degree. The results showed a social mobility framework in relation to the original group through the occupation of highly prestigious positions within the careers (Vargas, H., 2010) and incomes compatible with this occupation. The cultural consumption was homogeneous (Lahire, 2004; 2006; Setton, 2008; 2010), being linked to the cultural background that the alumni had prior to university, to the classmates' cultural characteristics with whom they interact during university life, and also to the individuals' cultural background with whom the surveyed individuals have related emotionally. However, it was observed a strong recognition of legitimate recognized culture. Regarding the formation of the social capital, the research showed that graduating from one of these schools allowed a more fluid mobility in the different social environments and sociability networks, highlighted by the interviewees' emotional/matrimonial relationships with individuals with heightened sociocultural profiles, and by forging a network of relationships that could be mobilized for obtaining information and being appointed within the job market.